Consumption habits and electronic commerce in Lima millennials - COVID-19/2021 pandemic - Angulo Espinoza, Vanessa Estefanía; Mongrut Tello, Patricia del Pilar; Napán Yactayo, Ana Cecilia (Cuadernos de Administración, 2022)
Worldwide, and specifically in Peru because of the Covid-19 pandemic, different types of human behavior have been modified due to quarantines imposed by the government. This meant a strict change in the modality in which consumers acquired products or services. Lima millennials represent 32.1% of the population. They had to adapt their consumption habits to the novelties imposed by electronic commerce. This is how, as of 2021, electronic commerce became relevant in face of restrictions on the movement of people. Therefore, from the point of view of this study, the objective of the investigation considers “determining if consumption habits are related to electronic commerce in Lima millennials - Covid-19/2021 pandemic”. Regarding the methodology, the non-experimental design was implemented, a cross-sectional study with a quantitative approach, and correlational descriptive scope. The sample was probabilistically calculated through the formula for finite population proportions with a result of 384 people between 23 and 37 years old (millennials). For obtaining the data, the survey was used as a technique, as well as a questionnaire as an instrument made up of 28 items for both variables. For data processing in the inferential environment according to the normality test, Spearman’s Rho statistician was used, finding positive correlations. About the general hypothesis, the correlation was (r = 0,371) indicating that the relationship is positive, concluding that consumption habits are significantly related to electronic commerce in Lima millennials - Covid-19/2021 pandemic.